Impact of "critical lesions" on outcomes following cytoreductive surgery and hyperthermic intra-peritoneal chemotherapy. Issue 11 (November 2021) - Ben-Yaacov, A.; Laks, S.; Goldenshluger, M.; Nevo, Y.; Mor, E.; Schtrechman, G.; Margalit, O.; Boursi, B.; Shacham-Shmueli, E.; Halpern, N.; Purim, O.; Hazzan, D.; et al.
Abstract: Background: Peritoneal Cancer Index (PCI) and complete cytoreduction are the best outcome predictors following cytoreductive surgery (CRS) with hyperthermic intraperitoneal chemotherapy (HIPEC). Lesions in critical areas, regardless of PCI, complicate surgery and impact oncological outcomes. We prospectively defined "Critical lesions" (CL) as penetrating the hepatic hilum, diaphragm at hepatic outflow, major blood vessels, pancreas, or urinary tract. Methods: Retrospective analysis of a prospective database of 352 CRS + HIPEC patients from 2015 to 2019. Excluded patients with aborted/redo operation ( n  = 112), or incomplete data ( n  = 19). Patients categorized by CL status and compared: operative time, estimated blood loss (EBL), PCI, transfusions, hospital stay, post-operative complications and mortality, overall survival (OS) and disease-free survival (DFS). Results: Included 221 patients (78 CL; 143 no-CL). No difference in patients' characteristics: age, BMI, gender or co-morbidities noted. Operative time longer (5.3 h vs 4.3 h, p  < 0.01), EBL higher (769 ml vs 405 ml, p  < 0.01), transfusions higher (1.9 vs 0.7 Units, p  < 0.001) and PCI higher (15.5 vs 9.5, p  < 0.01) in CL. No difference in major complications. Postoperative complications, CL, OR-time and transfusions were predictive of OS in univariate analysis, while only complications remained on multivariate analysis. Median follow up of 21.4 months, 3-year DFS/OS was 22% vs 30% ( p  < 0.037) and 73% vs 87% ( p  < 0.014) in CL and non-CL, respectively. Despite CL complete resection, 17/38 patients (44.7%) that recurred had recurrence at previous CL site. Conclusions: Critical lesions complicate surgery and may be associated with poor oncological outcomes with high local recurrence rate, despite no significant difference in complications. Utilizing adjuvant or intra-operative radiation may be beneficial.